Avaliação das atividades Anti-Trypanosoma cruzi e imunomoduladora de extrato de folhas de embaúba (Cecropia pachystachya Trécul) in vivo E in vitro. - Nicolau, Scheila Thaís (2023)
Chagas Disease (CD), American trypanosomiasis, is a fatal parasitic disease. It is caused by the protozoan Trypanosoma cruzi, with its primary vector being a hematophagous triatomine bug, commonly known as the "kissing bug." One of the crucial aspects influencing the course of CD is the immune response, as clinical manifestations depend on factors inherent to both the parasite and the host. Its treatment is partially effective, relying on medications such as Benznidazole (BZN) and Nifurtimox, which are more effective when administered during the acute phase. However, their efficacy diminishes over time, and adverse effects may occur. Cecropia pachystachya, a plant known as "embaúba" and utilized in traditional medicine for various properties, including anti-inflammatory action, contains ursolic acid as one of its components. Ursolic acid has demonstrated trypanocidal activity in CD, inhibiting the parasite in mouse experiments. Studies involving the embaúba plant may offer hope in the search for new treatment options with fewer adverse effects. This study aimed to assess the in vitro action of Cecropia pachystachya extract through its anti-Trypanosoma cruzi activity on amastigote forms within murine peritoneal macrophages. In vivo experiments were also conducted to analyze the extract's toxicity in non-infected animals and its activity in the acute experimental infection of T. cruzi in mice (BALB/c and C57Bl/6). In vitro activity revealed that the embaúba extract inhibited nitrite production at all concentrations, with significant inhibition observed at 300 µg/mL. Assessing extract toxicity regarding blood leukocytes in non-infected animals showed a more substantial reduction in the group treated with the extract. In experiments with infected animals, susceptible BALB/c mice treated with the extract exhibited a 40% survival rate at the end, remaining the only group that did not significantly decrease blood leukocyte count. Additionally, this group prevented a significant increase in spleen size compared to other groups. Concerning TNF-alpha and IL-6 cytokines in BALB/c animals' serum, the BZN treated group exhibited decreased levels, likely due to the drug's action in reducing parasite load. In resistant C57Bl/6 animals, the extract reduced parasitemia and showed comparable survival rates to the BZN-treated group. Nitrite production analysis revealed that the BZN-treated group had the lowest production. In contrast, the BZN-extract combination group had the highest, suggesting the embaúba extract may interfere with increased nitric oxide production. Regarding pro-inflammatory cytokine IL-6 concentrations, it can be inferred that C. pachystachya extract did not decrease its production compared to the untreated control group, which exhibited the lowest IL-6 concentration.